Chlojapolactone A, an unprecedented 1, 3-dioxolane linked-lindenane sesquiterpenoid dimer from Chloranthus japonicus. Issue 125 (1st December 2015) - Guo, Yan-Qiong; Tang, Gui-Hua; Li, Zhen-Zhen; Lin, Shu-Ling; Yin, Sheng
Abstract : Chlojapolactone A (1 ), a novel lindenane sesquiterpenoid dimer with an unprecedented 1, 3-dioxolane linkage, was isolated from Chloranthus japonicus . Abstract : Chlojapolactone A (1 ), a novel lindenane sesquiterpenoid dimer with an unprecedented 1, 3-dioxolane linkage, was isolated from Chloranthus japonicus . Its structure and absolute configuration was elucidated by combined spectral, computational, and chemical approaches. Compound1 exhibited potential inhibitory effects on nitric oxide production in RAW 264.7 cells.